2016
DOI: 10.1158/0008-5472.can-16-1260
|View full text |Cite
|
Sign up to set email alerts
|

Humanized Mouse Xenograft Models: Narrowing the Tumor–Microenvironment Gap

Abstract: Cancer research has long been hampered by the limitations of the current model systems. Both cultured cells and mouse xenografts grow in an environment highly dissimilar to that of their originating tumor, frequently resulting in promising treatments that are ultimately clinically ineffective. The development of highly immunodeficient mouse strains into which human immune systems can be engrafted can help bridge this gap. Humanized mice (HM) allow researchers to examine xenograft growth in the context of a hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
154
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 48 publications
1
154
0
11
Order By: Relevance
“…If speciesspecific factors are subject of research, one possible bypass is the use of humanized mouse acceptors. Humanized substrains of NSG and NOG expressing species-specific human cytokines, growth factors, receptors, histocompatibility antigens or adhesion molecules, or harboring even functional human hematopoietic stem cells or tissues such as bone marrow, liver, and thymus are under development to address questions related to human immune cells and stem cells within their niche (39,41) as well as virus (EBV and HCV)-related aspects of cancer (42). In contrast, syngeneic, immune-compatible transplanted cells are not rejected by the host organism.…”
Section: Cell-based Transplantation Modelsmentioning
confidence: 99%
“…If speciesspecific factors are subject of research, one possible bypass is the use of humanized mouse acceptors. Humanized substrains of NSG and NOG expressing species-specific human cytokines, growth factors, receptors, histocompatibility antigens or adhesion molecules, or harboring even functional human hematopoietic stem cells or tissues such as bone marrow, liver, and thymus are under development to address questions related to human immune cells and stem cells within their niche (39,41) as well as virus (EBV and HCV)-related aspects of cancer (42). In contrast, syngeneic, immune-compatible transplanted cells are not rejected by the host organism.…”
Section: Cell-based Transplantation Modelsmentioning
confidence: 99%
“…In particular, the authors observed that the stroma surrounding the tumors had human T and B cell infiltration, the stromal microenvironment was reprogrammed, with alteration of gene expressions governing the extracellular matrix, the immune response, and the epithelial-mesenchymal transition. 44 Importantly, humanized mice may be useful not only for studying human diseases but also for discovering more effective anticancer therapies. Even though we are still in the early stages of this type of technology, there are several recently published studies showing the utility of humanized mice in the development of immunomodulatory anticancer agents.…”
Section: Mouse Species Advantages Limitationsmentioning
confidence: 99%
“…44 In this review, one of the main key points raised was in regard to the eventual presence of mature xenoreactive T cells in humanized mice created by the injection of purified CD34+ cells. In this case, T cells could recognize tumor cells as a foreign body and possibly kill them as it was observed that tumors implanted in humanized mice grow more slowly than tumors implanted on the same non-humanized mice strain.…”
Section: Mouse Species Advantages Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humanized mouse models have been extensively used to study human diseases and virus pathogenesis (21)(22)(23)(24)(25)(26)(27)(28). These models reconstitute the microenvironment of the human lung to evaluate the host response during virus infection in the human lung.…”
mentioning
confidence: 99%